2020
DOI: 10.2144/fsoa-2020-0140
|View full text |Cite
|
Sign up to set email alerts
|

The Enigmatic Helicase DHX9 and Its Association With the Hallmarks of Cancer

Abstract: Much interest has been expended lately in characterizing the association between DExH-Box helicase 9 (DHX9) dysregulation and malignant development, however, the enigmatic nature of DHX9 has caused conflict as to whether it regularly functions as an oncogene or tumor suppressor. The impact of DHX9 on malignancy appears to be cell-type specific, dependent upon the availability of binding partners and activation of inter-connected signaling pathways. Realization of DHX9’s pivotal role in the development of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 119 publications
(162 reference statements)
1
24
1
Order By: Relevance
“… 59 The involvement of DHX9 in malignancies makes it an attractive biomarker and target for cancer therapy. 60 In our research, DHX9 was overexpressed in stage II in B cells of the CRC-adjacent tissue ( Figure 5 B). DHX9 and its related genes such as STRAP, CHO4 , and SNRPB2 exhibited a synergistic change at the network level ( Figure S8 ).…”
Section: Discussionsupporting
confidence: 51%
“… 59 The involvement of DHX9 in malignancies makes it an attractive biomarker and target for cancer therapy. 60 In our research, DHX9 was overexpressed in stage II in B cells of the CRC-adjacent tissue ( Figure 5 B). DHX9 and its related genes such as STRAP, CHO4 , and SNRPB2 exhibited a synergistic change at the network level ( Figure S8 ).…”
Section: Discussionsupporting
confidence: 51%
“… 6 Much effort has been expended lately in characterizing the association between DHX9 dysregulation and cancer development; however, there is still conflict as to whether it regularly functions as an oncogene or tumor suppressor. 11 The effect of DHX9 on cancers appears to be cell‐type specific, dependent on the kind of binding partners. 11 , 12 Some studies suggested that DHX9 functioned as an oncogene and highly expressed in cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“… 11 The effect of DHX9 on cancers appears to be cell‐type specific, dependent on the kind of binding partners. 11 , 12 Some studies suggested that DHX9 functioned as an oncogene and highly expressed in cancer tissues. 13 Palombo et al 14 showed that poison‐exon inclusion in DHX9 by hnRNPM and SRSF3 reduced its expression and inhibited cell proliferation in Ewing sarcoma malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was also shown to modulate circulatory RNAs during EMT. (238). Ring1b, a core component of the Polycomb Repressive Complex 1 (PRC1) has been shown to form complex with DEAD-box RNA helicases such as DDX3X and DDX5 and downregulate E-cadherin by binding to its promoter.…”
Section: Elk3 Has Been Shown To Positively Influence Emt In Breast Cancer Cells As Well As During Progressionmentioning
confidence: 99%